Lithostratigraphy of Zechstein evaporites of the central and north-western parts of the Mogilno Salt Diapir, based on boreholes Z-9 and Z-17 - WACHOWIAK, Jacek; PAWLIKOWSKI, Maciej; WILKOSZ, Paweł (Geology, Geophysics and Environment, 2012)
This paper presents the results of comprehensive mineralogical and petrographic studies conducted on evaporite rocks of the Zechstein (Upper Permian) period, extracted from boreholes drilled in the Mogilno diapir. Based on the research results, the occurrence of rock salts, potash-magnesium salts (kieseritic sylvinites), clayey salts, zubers, and anhydrites was identified. Those formations were assigned to cyclothems PZ-3 and PZ-2. No presence of evaporites belonging to cyclothems PZ-1 and PZ-4 were discovered. The recognized rocks were mainly composed of halite, sylvine, kieserite and anhydrite. Smaller quantities of polyhalite, kainite, carbonates and clayey minerals were also found. A number of accessory minerals were identified, with their salt rock contents from several to about several tens of ppm.